2015
DOI: 10.1363/47e4215
|View full text |Cite
|
Sign up to set email alerts
|

STD and Abortion Prevalence in Adolescent Mothers With Histories of Childhood Protection Involvement

Abstract: To assess whether adolescents with a history of CPS involvement need targeted sexual health interventions, further research is needed on the mechanisms that underlie associations between CPS involvement and adverse sexual health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…28,29 The results showed that China's college students have a lower proportion of early sexual debut compared with other studies, 30 which may indicate the relatively conservative attitude towards sex among Chinese college students 31 However, a considerable number of Chinese students have sexual debut at an early age, which may bring negative health consequences to them, including unplanned pregnancy and sexually transmitted infections. 32 Consistent with previous researches, 22,33 our findings showed that college students tended to have multiple sexual partners, which is a great risk factor for HIV/STD infection. 34 More attention should be paid to this phenomenon, especially in the context of China, where there is not enough formal and comprehensive sexual education and counseling for adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…28,29 The results showed that China's college students have a lower proportion of early sexual debut compared with other studies, 30 which may indicate the relatively conservative attitude towards sex among Chinese college students 31 However, a considerable number of Chinese students have sexual debut at an early age, which may bring negative health consequences to them, including unplanned pregnancy and sexually transmitted infections. 32 Consistent with previous researches, 22,33 our findings showed that college students tended to have multiple sexual partners, which is a great risk factor for HIV/STD infection. 34 More attention should be paid to this phenomenon, especially in the context of China, where there is not enough formal and comprehensive sexual education and counseling for adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…A significant number of pregnant women appear to visit health facilities for emergency management of induced abortion (2). While those women with unwanted pregnancy and having an intention to stop at early weeks of gestation is one inevitable characteristic of this group, attendance following an intrauterine foetal death or viability failure, due to various causes, is frequently mentioned (3)(4)(5). Numerous studies indicate that using medications, especially mifepristone and misoprostol, is preferred over aspiration or curettage interventions for terminating a first trimester pregnancy (6,7) or evacuating an early pregnancy failure (8).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, those women with unwanted pregnancy and having an intention to stop at early weeks of gestation are one inevitable aspect of this group, attendance following an intrauterine fetal death or viability failure, due to various causes, is frequently mentioned [3][4][5].This review will consider articles which included pregnant women up to 12 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%